High-ductility geopolymer composite material as well as preparation method and application thereof

By using materials such as steel slag powder, fly ash, slag powder and alkaline exciters, combined with polyethylene fibers, high ductility polymer composite materials are prepared, which solves the problems of environmental pollution and high cost of cement-based composite materials in the prior art, and achieves efficient and low-cost high ductility material preparation.

CN119774934APending Publication Date: 2025-04-08SHENZHEN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411987772.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing high-strength and high-ductility cement-based composite materials require a large amount of cement and fiber during the preparation process, resulting in environmental pollution and high costs, while their ductility properties are limited.

Method used

Highly ductile geopolymer composite materials are prepared by materials such as steel slag powder, fly ash, slag powder, alkaline exciters and polyethylene fibers. The preparation of alkali excitation reactions is replaced by cement preparation, reducing carbon dioxide emissions, and optimizing the fiber usage to improve ductility.

Benefits of technology

The preparation of high-ductility geopolymer composite materials is realized, which reduces preparation costs, reduces environmental pollution, and meets the requirements of high-strength and high-ductility composite materials in terms of tensile properties and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774934A_ABST
    Figure CN119774934A_ABST
Patent Text Reader

Abstract

The invention provides a high-ductility geopolymer composite material as well as a preparation method and application thereof, and belongs to the technical field of building materials. The high-ductility geopolymer composite material provided by the invention is prepared from the following components in parts by mass: 10 to 30 parts of steel slag powder, 25 to 50 parts of fly ash, 45 to 50 parts of mineral slag powder, 28 to 34 parts of alkaline excitant, 1.4 to 1.7 parts of polyethylene fiber, 23 to 26 parts of silica sand, 10 to 12 parts of retarder and 25 to 29 parts of water, the alkaline exciting agent is NaOH and water glass; and the length of the polyethylene fiber is greater than or equal to 18mm. The steel slag powder is used as the raw material, the preparation cost is reduced, the alkali-activated material is used for replacing cement to prepare the ECC, good performance can be achieved, carbon dioxide is basically not discharged in the production process, the problem of carbon emission is effectively solved, and green benefits are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a high-ductility geopolymer composite material and a preparation method and application thereof. Background Art

[0002] In order to solve the brittleness problem of concrete for construction, scholars have invented a high-strength and high-ductility cement-based composite material (High-strength and High-ductility ECC, referred to as HSHD-ECC), which has a ductility of 400 times or more than that of ordinary concrete, an ultimate elongation of more than 2%, and exhibits its tensile ductility in the form of multi-crack cracking. HSHD-ECC is mainly made of cement, mineral admixtures, fine aggregates, fibers, and admixtures. HSHD-ECC requires a large amount of cement and fiber. The preparation process of cement will emit a large amount of carbon dioxide, posing a threat to the environment. In order to achieve higher ductility, a large amount of fiber is required, which leads to high cost of ECC and limited application.

[0003] Among them, high-ductility geopolymer composite materials are a kind of high-strength and high-ductility cement-based composite materials. The relevant technology discloses a method for preparing high-ductility geopolymer composite materials, which uses slag, fly ash, waste fine brick sand, and polyvinyl alcohol fiber (PVA) as raw materials to prepare geopolymer composite materials (Engineered Geopolymer Composite, EGC). This method requires manual crushing of fine brick sand, which increases the process steps and improves the time cost. The hardness of the used waste fine brick sand is low, which is not conducive to the strength development of EGC. At the same time, the PVA fiber itself is a hydrophilic fiber. As the strain hardening continues, the chemical bonding strength of the PVA fiber / matrix interface continues to increase, which is not conducive to EGC maintaining good strain hardening properties and is not conducive to the fiber playing a bridging role, resulting in reduced ductility. Summary of the invention

[0004] The object of the present invention is to provide a high-ductility geopolymer composite material and a preparation method and application thereof. The geopolymer composite material provided by the present invention has high ductility, and the preparation method is simple and the cost is lower.

[0005] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0006] A high-ductility geopolymer composite material, comprising the following raw materials by weight:

[0007] 10-30 parts of steel slag powder, 25-50 parts of fly ash, 45-50 parts of slag powder, 28-34 parts of alkaline activator, 1.4-1.7 parts of polyethylene fiber, 23-26 parts of silica sand, 10-12 parts of retarder and 25-29 parts of water;

[0008] The alkaline activator is NaOH and water glass; the length of the polyethylene fiber is ≥18mm.

[0009] Preferably, the fly ash is Class F fly ash; the slag powder is Class S95 slag powder;

[0010] The particle sizes of the fly ash and slag powder are independently 400-500 meshes.

[0011] Preferably, the particle size of the steel slag powder is 180-250 mesh.

[0012] Preferably, the purity of the silica sand is 98-99.6% and the particle size is 70-110 meshes.

[0013] Preferably, the modulus of the alkaline activator is 1.2 to 1.6.

[0014] Preferably, the retarder is industrial sucrose and borax; the mass ratio of the industrial sucrose and borax is 3.1-5.7:6.3-9.9.

[0015] Preferably, the polyethylene fiber has a diameter of 22 to 27 μm, an aspect ratio of 652 to 841, an elastic modulus of 114 to 150 GPa, a uniaxial tensile strength of 2809 to 3004 MPa, and a density of 0.95 to 0.98 gm / cm 3 .

[0016] The present invention also provides a method for preparing the high-ductility geopolymer composite material described in the above technical solution, comprising the following steps:

[0017] Firstly mixing steel slag powder, fly ash, slag powder, silica sand and retarder to obtain a first mixture;

[0018] The first mixture, the alkaline activator and water are mixed for a second time to obtain a second mixture;

[0019] The second mixed material and the polyethylene fiber are mixed for the third time to obtain the high ductility geopolymer composite material.

[0020] Preferably, the second mixing includes low-speed stirring and high-speed stirring in sequence; the rate of the low-speed stirring is 135-145 r / min; the rate of the high-speed stirring is 275-295 r / min.

[0021] The present invention also provides the use of the high-ductility geopolymer composite material described in the above technical solution or the high-ductility geopolymer composite material prepared by the preparation method described in the above technical solution in the reinforcement of concrete structures, masonry structures or the rapid repair of concrete pavements.

[0022] The present invention provides a high-ductility geopolymer composite material, which includes the following raw materials by weight: 10-30 parts of steel slag powder, 25-50 parts of fly ash, 45-50 parts of slag powder, 28-34 parts of alkaline activator, 1.4-1.7 parts of polyethylene fiber, 23-26 parts of silica sand, 10-12 parts of retarder and 25-29 parts of water; the alkaline activator is NaOH and water glass; the length of the polyethylene fiber is ≥18mm. The present invention uses steel slag powder as raw material, improves the utilization rate of steel slag powder, reduces the preparation cost, and the alkaline activator of the present invention is NaOH and water glass. The use of alkaline activator materials to replace cement to prepare ECC can not only achieve good performance, but also the production process basically does not emit carbon dioxide, effectively solves the carbon emission problem, and improves green benefits. At the same time, the present invention uses fly ash and slag powder as cementitious materials, and cooperates with alkaline activators to stimulate the activity of geopolymers. The amount of fiber used is half of that of ordinary ECC materials. On the basis of realizing the recycling of solid waste and reducing material costs, the tensile properties and mechanical properties can also meet the requirements of high-strength and high-ductility composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 This is the particle size distribution diagram of slag powder and fly ash;

[0025] Figure 2 This is the particle size distribution diagram of steel slag powder;

[0026] Figure 3 The uniaxial tensile curve of the high ductility geopolymer composite material prepared in Example 1;

[0027] Figure 4 is a uniaxial tensile curve diagram of the high ductility geopolymer composite material prepared in Example 2;

[0028] Figure 5 The uniaxial tensile curve of the high ductility geopolymer composite material prepared in Example 3;

[0029] Figure 6 This is a bar graph of the compressive strength of the high ductility geopolymer composite materials prepared in Examples 1 to 3 and Comparative Example 1 at 7d and 28d. DETAILED DESCRIPTION

[0030] The present invention provides a high-ductility geopolymer composite material, which comprises the following raw materials by weight:

[0031] 10-30 parts of steel slag powder, 25-50 parts of fly ash, 45-50 parts of slag powder, 28-34 parts of alkaline activator, 1.4-1.7 parts of polyethylene fiber, 23-26 parts of silica sand, 10-12 parts of retarder and 25-29 parts of water;

[0032] The alkaline activator is NaOH and water glass; the length of the polyethylene fiber is ≥18mm.

[0033] In the present invention, unless otherwise specified, all preparation raw materials are preferably commercially available products well known to those skilled in the art.

[0034] In the present invention, the high ductility geopolymer composite material includes 10 to 30 parts of steel slag powder by mass, and in a specific embodiment, it can be 10, 15 or 20 parts; the particle size of the steel slag powder can be 180 to 250 meshes, and in a specific embodiment, it can be 180 meshes, 200 meshes or 250 meshes. In the present invention, the steel slag powder is low in cost, and its effective use can alleviate the serious waste of resources and environmental pollution problems; and the steel slag powder contains a certain amount of free CaO and MgO, has hydraulic activity, and its activity can be activated by alkali, and is very suitable for being incorporated into the alkali-activated geopolymer system.

[0035] In the present invention, the high-ductility geopolymer composite material includes 25 to 50 parts of fly ash by mass, and in a specific embodiment, it can be 30, 40 or 45 parts; the fly ash can be low-calcium F-class fly ash; the particle size of the fly ash can be 400 to 500 meshes, and in a specific embodiment, it can be 450 or 480 meshes.

[0036] In the present invention, the high ductility geopolymer composite material includes 45-50 parts of slag powder by weight, and in a specific embodiment, it can be 45, 48 or 50 parts; the slag can be S95 grade slag; the particle size of the fly ash can be 400-500 meshes, and in a specific embodiment, it can be 450 or 480 meshes. In the present invention, slag powder and fly ash are used as gel materials, and the two are used in combination, which can give full play to their active characteristics, so that the concrete has appropriate strength in the early and late stages, and can improve the material's resistance to chloride ion corrosion and late strength.

[0037] In the present invention, the high ductility geopolymer composite material includes 28 to 34 parts of alkaline activator by mass, and in a specific embodiment, it can be 28, 30 or 34 parts; the alkaline activator is NaOH and water glass; the modulus of the alkaline activator can be 1.2 to 1.6, and in a specific embodiment, it can be 1.3, 1.4 or 1.5; the alkali equivalent of the alkaline activator can be 5% to 7%, and in a specific embodiment, it can be 5%, 6% or 7%. In the present invention, using alkaline activator to replace cement to prepare ECC can not only achieve good performance, but also the production process basically does not emit carbon dioxide, effectively solving the carbon emission problem and improving green benefits.

[0038] In the present invention, the high ductility geopolymer composite material includes 1.4 to 1.7 parts of polyethylene fiber (PE) by mass, and in a specific embodiment, it can be 1.5 or 1.6 parts; in a specific embodiment, it can be PE fiber; the length of the polyethylene fiber is ≥18 mm, and in a specific embodiment, it can be 18 mm, 20 mm or 22 mm; the diameter can be 22 to 27 μm, and in a specific embodiment, it can be 23, 25 or 26 μm; the aspect ratio can be 652 to 841, and in a specific embodiment, it can be 720, 652 or 841; the elastic modulus can be 114 to 150 GPa, and in a specific embodiment, it can be 116, 120 or 140 GPa; the tensile strength can be 2809 to 3004 MPa, and in a specific embodiment, it can be 2900, 2800 or 3000 MPa; the density can be 0.95 to 0.98 gm / cm 3 , in specific embodiments, can be 0.97, 0.95 or 0.98 gm / cm 3 In the present invention, the polyethylene fiber has the function of bridging microcracks in the matrix and limiting the expansion of the cracks, so that the material can withstand large strains without brittle failure when stretched or bent, and the obtained material is widely used in the repair and reinforcement of high-performance building materials, bridges, tunnels and other infrastructure.

[0039] In the present invention, the high ductility geopolymer composite material includes 23 to 26 parts of silica sand by mass, and in a specific embodiment, it can be 24, 25 or 26 parts; the purity of the silica sand can be 98 to 99.6%; the particle size can be 70 to 110 meshes, and in a specific embodiment, it can be 80, 90 or 100 meshes. In the present invention, the silica sand has a certain hardness and acts as a skeleton structure in the material, which can effectively alleviate the shrinkage cracking problem common in geopolymers.

[0040] In the present invention, the high ductility geopolymer composite material includes 10 to 12 parts of retarder by weight, and in a specific embodiment, it can be 10, 11 or 12 parts; the retarder can be industrial sucrose and borax; the mass of the industrial sucrose and borax can be 2.1 to 5.7:6.3 to 9.9, and in a specific embodiment, it can be 3:7, 4:7 or 4:8. In the present invention, the addition of the retarder can effectively delay the setting time of the slurry, help improve the working performance of the geopolymer, and prevent the mixture from hardening too quickly. In addition, the uniformity and dispersion of the material are improved.

[0041] The present invention also provides a method for preparing the high-ductility geopolymer composite material described in the above technical solution, comprising the following steps:

[0042] Firstly mixing steel slag powder, fly ash, slag powder, silica sand and retarder to obtain a first mixture;

[0043] The first mixture, the alkaline activator and water are mixed for a second time to obtain a second mixture;

[0044] The second mixed material and the polyethylene fiber are mixed for the third time to obtain the high ductility geopolymer composite material.

[0045] In the present invention, the first mixing method can be stirring mixing; the first mixing rate can be 135-145r / min, and in a specific embodiment, it can be 135, 140 or 145r / min; the time can be 1-3min, and in a specific embodiment, it can be 1.5, 2 or 3min.

[0046] In the present invention, the second mixing includes low-speed stirring and high-speed stirring in sequence; the rate of the low-speed stirring can be 135-145 r / min, and the time can be 0.5-1 min; the rate of the high-speed stirring can be 275-295 r / min, and in a specific embodiment, it can be 280, 285 or 290 r / min, and the time can be 0-1.5 min, and in a specific embodiment, it can be 0.5, 1 or 1.5 min.

[0047] In the present invention, the third mixing method can be stirring mixing; the third mixing rate can be 275-295r / min, and in a specific embodiment, it can be 280, 285 or 290r / min; the time can be 10-20min, and in a specific embodiment, it can be 10, 13 or 18min.

[0048] In the present invention, the third mixing also includes molding, demolding and curing the obtained mixture in sequence; the present invention has no special limitation on the mold used for the molding; the curing in the present invention is carried out under standard humidity and standard temperature conditions; the curing time can be 7 to 28 days, and in a specific embodiment, it can be 7 days or 28 days.

[0049] The present invention also provides the use of the high-ductility geopolymer composite material described in the above technical solution or the high-ductility geopolymer composite material prepared by the preparation method described in the above technical solution in the reinforcement of concrete structures, masonry structures or the rapid repair of concrete pavements.

[0050] In order to further illustrate the present invention, the high ductility geopolymer composite material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0051] The particle size distribution diagram of slag powder, fly ash and steel slag powder in the following embodiments of the present invention is as follows: Figures 1-2 shown.

[0052] Example 1

[0053] Weigh 40 parts of Class F fly ash, 50 parts of slag powder, 10 parts of steel slag powder, 32 parts of 1.5 modulus alkaline activator, 25 parts of water, 25 parts of high-purity silica sand, 1.5 parts of fiber and 10 parts of retarder for use;

[0054] Dry mix fly ash, slag, steel slag powder, sand and retarder for 1.5 minutes at a mixer blade rotation frequency of 140 r / min; add alkaline activator and water, stir at 140 r / min for 1 minute, and then stir at 285 r / min for 0.5 minutes; add fiber and stir for 10 minutes; mold, cure at room temperature for 24 hours, then remove the mold, and seal and cure at standard temperature and humidity for 28 days.

[0055] Example 2

[0056] Weigh 40 parts of Class F fly ash, 50 parts of slag powder, 20 parts of steel slag powder, 32 parts of 1.5 modulus alkaline activator, 25 parts of water, 25 parts of high-purity silica sand, 1.5 parts of fiber and 10 parts of retarder for use;

[0057] Dry mix fly ash, slag, steel slag powder, sand and retarder for 1.5 minutes at a mixer blade rotation frequency of 140 r / min; add alkaline activator and water, stir at 140 r / min for 1 minute, and then stir at 285 r / min for 0.5 minutes; add fiber and stir for 10 minutes; mold, cure at room temperature for 24 hours, then remove the mold, and seal and cure at standard temperature and humidity for 28 days.

[0058] Example 3

[0059] Weigh 40 parts of Class F fly ash, 50 parts of slag powder, 30 parts of steel slag powder, 32 parts of 1.5 modulus alkaline activator, 25 parts of water, 25 parts of high-purity silica sand, 1.5 parts of fiber and 10 parts of retarder for use;

[0060] Dry mix fly ash, slag, steel slag powder, sand and retarder for 1.5 minutes at a mixer blade rotation frequency of 140 r / min; add alkaline activator and water, stir at 140 r / min for 1 minute, and then stir at 285 r / min for 0.5 minutes; add fiber and stir for 10 minutes; mold, cure at room temperature for 24 hours, then remove the mold, and seal and cure at standard temperature and humidity for 28 days.

[0061] Comparative Example 1

[0062] Weigh 40 parts of Class F fly ash, 50 parts of slag powder, 10 parts of steel slag powder, 32 parts of 1.2 modulus alkaline activator, 25 parts of water, 25 parts of high-purity silica sand, 1.5 parts of 12 mm fiber and 10 parts of retarder for use;

[0063] Dry mix fly ash, slag, steel slag powder, sand and retarder for 1.5 minutes at a mixer blade rotation frequency of 140 r / min; add alkaline activator and water, stir at 140 r / min for 1 minute, and then stir at 285 r / min for 0.5 minutes; add fiber and stir for 10 minutes; mold, cure at room temperature for 24 hours, then remove the mold, and seal and cure at standard temperature and humidity for 28 days.

[0064] Test Case

[0065] With reference to ASTM C1609 / C1609M and JGJ / T20-2009 "Standard Test Methods for Basic Properties of Building Mortar", the uniaxial tensile strength and compressive strength of the high ductility geopolymer composite materials prepared in Examples 1 to 3 were tested respectively. According to the recommendation of the Japan Society of Civil Engineers (JSCE), dog-bone-shaped uniaxial tensile test specimens were cast, and a 300kN MTS microcomputer-controlled electronic universal testing machine was used to load the uniaxial tensile test. The size of the compressive strength test specimen is 50×50×50mm. At least 3 specimens are made with the same ratio. After the specimens are demolded, they are cured in a standard curing room until the test age for testing. The test was carried out using an MTS200T pressure testing machine, and the test was carried out using a stress control method and a loading rate of 0.5MPa / s. The test results are shown below.

[0066] Figure 3 : is a uniaxial tensile curve of the high ductility geopolymer composite material prepared in Example 1, Figure 4is a tensile curve diagram of the high ductility geopolymer composite material prepared in Example 2, Figure 5 is a tensile curve diagram of the high ductility geopolymer composite material prepared in Example 3; Figures 3 to 5 It can be seen that the elongation of the geopolymer composite materials prepared in Examples 1 to 3 is between 4% and 5%, which is 40 to 50 times that of ordinary concrete. They have extremely high ductility and can withstand deformation of about 40 times that of traditional concrete when stretched without breaking. The difference between the geopolymer composite materials prepared in Examples 1 to 3 is the amount of steel slag powder added. The amount of steel slag powder added in the geopolymer composite materials prepared in Examples 1 to 3 gradually increases. Example 1 has the least amount of steel slag powder added, and the elongation can reach 5%. The elongation of Examples 2 and 3 is about 4%. This is because as the amount of steel slag powder increases, the material inhomogeneity in the matrix increases, and it is easier to produce a single through crack when stretched, which is not conducive to the development of multiple cracks, thereby affecting the tensile performance.

[0067] Figure 6 The compressive strength bar graphs of the high ductility geopolymer composite materials prepared in Examples 1 to 3 and Comparative Example 1 at 7d and 28d are shown in FIG. Figure 6 It can be seen that the 28d compressive strength of Examples 1 to 3 is all above 60 MPa, and as the amount of steel slag decreases, the compressive strength gradually increases. This is because the activity of steel slag powder is lower than that of fly ash, and replacing fly ash in equal amounts reduces the activity of the matrix gelling reaction.

[0068] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A high ductility geopolymer composite material, characterized in that: The preparation materials include the following by weight: 10-30 parts of steel slag powder, 25-50 parts of fly ash, 45-50 parts of slag powder, 28-34 parts of alkaline activator, 1.4-1.7 parts of polyethylene fiber, 23-26 parts of silica sand, 10-12 parts of retarder and 25-29 parts of water; The alkaline activator is NaOH and water glass; the length of the polyethylene fiber is ≥18mm.

2. The high ductility geopolymer composite material according to claim 1, characterized in that: The fly ash is F-grade fly ash; the slag powder is S95-grade slag powder; The particle sizes of the fly ash and slag powder are independently 400-500 meshes.

3. The high ductility geopolymer composite material according to claim 1, characterized in that: The particle size of the steel slag powder is 180-250 meshes.

4. The high ductility geopolymer composite material according to claim 1, characterized in that: The purity of the silica sand is 98-99.6%, and the particle size is 70-110 meshes.

5. The high ductility geopolymer composite material according to claim 1, characterized in that: The modulus of the alkaline activator is 1.2 to 1.

6.

6. The high ductility geopolymer composite material according to claim 1, characterized in that: The retarder is industrial sucrose and borax; the mass ratio of the industrial sucrose and borax is 3.1-5.7:6.3-9.

9.

7. The high ductility geopolymer composite material according to claim 1, characterized in that: The polyethylene fiber has a diameter of 22 to 27 μm, an aspect ratio of 652 to 841, an elastic modulus of 114 to 150 GPa, a uniaxial tensile strength of 2809 to 3004 MPa, and a density of 0.95 to 0.98 gm / cm 3 .

8. The method for preparing the high ductility geopolymer composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Firstly mixing steel slag powder, fly ash, slag powder, silica sand and retarder to obtain a first mixture; The first mixture, the alkaline activator and water are mixed for a second time to obtain a second mixture; The second mixed material and the polyethylene fiber are mixed for the third time to obtain the high ductility geopolymer composite material.

9. The preparation method according to claim 8, characterized in that: The second mixing includes low-speed stirring and high-speed stirring in sequence; the rate of the low-speed stirring is 135-145 r / min; the rate of the high-speed stirring is 275-295 r / min.

10. Use of the high-ductility geopolymer composite material according to any one of claims 1 to 7 or the high-ductility geopolymer composite material prepared by the preparation method according to claim 8 or 9 in the reinforcement of concrete structures, masonry structures or the rapid repair of concrete pavements.

Citation Information

Patent Citations

  • Early-strength ultrahigh-ductility geopolymer concrete material and preparation method thereof

    CN113800829A

  • High-ductility geopolymer composite material and preparation method thereof

    CN114853394A

  • Steel slag modified high-ductility geopolymer composite material as well as preparation method and application thereof

    CN117003517A

  • Ultrahigh-toughness geopolymer composite material and preparation method thereof

    CN117088650A

  • Coal gangue-slag-fly ash-based alkali-activated composite material and preparation method thereof

    CN118851642A